Mechanistic modeling to address process analysis: Kibbles of carob (Ceratonia siliqua, L.) pod extraction. (May 2016) - Mulet, A.; Fernández-Salguero, J.; García-Pérez, J.V.; Bon, J.
Abstract: The daily challenge involved in operating a process is the attainment of the objectives. Process management requires the use of tools adapted to the system's complexity. In order to obtain real time results, simplified mechanistic modeling offers a way to deal with this. To this end, carob pod ( Ceratonia siliqua, L.) kibbles extraction is addressed in this work. They are a source of different, valuable components and have a complex structure and a highly variable concentration of components. The components considered are sugars and soluble polyphenols. Obtaining the extracts with an optimal composition of a particular component, while avoiding or limiting other components in the extract, is a challenge to be addressed. Two steps can be considered: solubilization and diffusion, modeled by means of a first order reaction and by considering slab geometry. The optimal processing time and temperature are obtained by taking a particular kibble size and composition into account. Highlights: Complex raw materials extraction optimization. Mechanistic modeling allow real time process management. Solubilization and diffusion steps models for carob kibbles extraction. Decision tool to determine process variables to optimize the output.